Papunya Paintings : The Other Contemporary Art - Australian Summer. (Antwerpen : Ado Gallery, 1991)
Tjapaltjarri, Joseph Jurra ; Nungala, Iterlura ; Tjampitjinpa, Maxie ; Warankula Tjupurrula, Johnny ; Tjampitjinpa, Anatjari
Papunya Paintings : The Other Contemporary Art - Australian Summer, Ado Gallery Antwerpen Contemporary Art, 1991
boek
Keywords: Papunya Tula Artists